Effective carbon adsorbents of solid looping technologies for post combustion carbon capture - Liu, Jingjing (2017)
Carbon Capture and Storage (CCS) has been considered as one of the most promising techniques to reduce anthropogenic CO2 emissions in the atmosphere. As an alternative to replace the traditional technology of aqueous amine scrubbing, solid adsorbents looping technology (SALT) has attracted growing attention. Among various solid adsorbent materials, carbon-based materials with unique properties such as wide availability, relatively low cost, highly porous structure ease of regeneration, and stable cyclic performance, have been considered as promising candidates at both low pressure and moderate to high partial pressure. In this PhD research, activated carbon spheres derived from two different precursors, which are phenolic resin and coal-tar pitch, have been prepared and modified with potassium intercalation to improve CO2 capture performance for post combustion carbon capture. The project aims to investigate the factors that affect CO2 adsorption performance for post combustion carbon capture. Firstly, series of spherical activated carbon beads (with a uniform diameter of ca. 0.6-0.8 mm) derived from phenolic resin have been developed and characterised. The results show that the surface polarity can be enhanced by potassium intercalation. The intercalation of potassium significantly increased the CO2 capacity of the AC beads by a factor of up to 2 at 0.15 bar while the effects of the treatment on their mechanical strength and morphological features were negligible at KOH/AC mass ratios of 0.3 and below. The factors other than adsorption that affect the performance of phenolic resin derived carbon spheres were also investigated in terms of adsorption kinetics, cyclic performance, heat of adsorption, the effect of moisture, and regeneration heat. Secondly, coal tar pitch derived activated carbons, with uniform spherical diameter of 1-2 mm were synthesised via two different activation approaches, which is firstly an initial steam activation followed by KOH activation, and secondly one-step KOH activation, both with mild KOH/carbon mass ratios. Samples prepared with one-step KOH activation method had shown a better microporous structure and a higher CO2 adsorption capacity. Owing to the narrow micropores and K-doping, the samples demonstrated outstanding CO2 capacities at relatively low CO2 partial pressure. Multicycle stability was examined over 50 cycles of adsorption and desorption, and both samples present excellent adsorption kinetics and regeneration ability. Finally, the volumetric CO2 uptake of best performing samples were also calculated and compared with other candidates. Based on our previous results, further investigation towards the influence of precursor materials and correlation between microporosity pore size ranging from 0.4 nm to 2 nm and CO2 uptakes have been carried out. Future work on how to improve the CO2 sorption performances of the studied materials has been proposed.